Changing the shift system in a mining company: An intervention study. Issue 2 (9th November 2017) - Castellucci, H. I.; Altamirano, I.
Abstract: The aim of this study is to determine the shift system that allows for sustainable time management, considering the characteristics of the mining company analyzed. Regarding the methodology, the Standard Shiftwork Index was used to characterize the workers perceptions of the shift system. In order to increase the chances of changing the shift system, the Besiak method of shifts was applied to the following: modified 4 × 4 (current shift); 6 × 6 modified and 7 × 7. Furthermore, with input from company representatives, the method seeks to jointly identify the company's strengths, weaknesses, opportunities, and threats of the different shift systems. The main results show that the level in which the shift system (modified 4 × 4) interferes with leisure, social, and domestic life is associated with the city of residence. The application of Besiak concluded that the order of the highest risk to the lowest risk is as follows: 7 × 7, modified 6 × 6, and modified 4 × 4. Once the 7 × 7 shift work was discarded, a second level of analysis was performed between the two remaining shift work systems. Both have strengths, but the worker's place of residence on the days off became the determining factor. Hence, the 6 × 6 modified model met the biopsychosocial factors and favored residence in other cities during the days off. Finally, it was clear that during the shift system change, it is very important to involve workers, labor unions, and managers in the process of designing and introducing a new shift system.